Borophene@HKUST-1 composite material based flexible electrodes for energy storage in supercapacitors - Penlik, Yunus; Artar, Emirhan; Gorduk, Ozge; Sahin, Yucel; Avciata, Oguzhan; Gorduk, Semih (ELSEVIER, 2025)
Nowadays, the interest in flexible and wearable electronic devices has stimulated the development of flexible supercapacitors with high capacities, long cycle life, and low cost. In this study, Borophene, a newcomer in the two-dimensional materials family, and HKUST-1 structure with its unique crystallinity and stable structure were synthesized. Then, the composite structure of these compounds (Borophene@HKUST-1) was synthesized for the first time by a simple mixing method. After, conductive inks were prepared using the obtained Borophene@HKUST-1 composite. The carbon felt electrodes, which allow the formation of flexible electrodes, are then coated with these conductive inks. The electrochemical behavior of these electrodes was then determined using cyclic voltammetry, electrochemical impedance spectroscopy, and galvanostatic charge-discharge methods. The performance of Borophene@HKUST-1 flexible electrode in supercapacitor applications was investigated and it was observed that it exhibited a high specific areal capacitance value of 333 mF/cm2 at a current density of 3 mA/cm2. At the end of 1000 cycles, it showed high stability by maintaining 63.4 % of its capacitance value.
Keywords: Energy storage; Borophene; Composite; Supercapacitor; HKUST-1; METAL-ORGANIC FRAMEWORKS; HIGH-PERFORMANCE; CARBON COMPOSITE; SQUARIC ACID; ADSORPTION; COMPLEXES; NANOSHEETS; LIQUID; Chemistry